Studi Literatur: Pengaruh Aplikasi Schoology pada Pembelajaran Matematika terhadap Hasil Belajar Siswa SMP - Dinda Dwi Kartiwati (MEGA: Jurnal Pendidikan Matematika, 2021)
AbstractResearchers conducted this study with the aim of describing the learning outcomes of junior high school students using the Schoology application in mathematics learning and the effect of the Schoology application of mathematics learning on junior high school student learning outcomes. Researchers use literature research methods with qualitative descriptive research. Researchers use data sources from articles and theses. Data collection techniques in this study using the documentation method. The data analysis technique use by the researcher is bibliographic analysis. The results of library research or this study are the learning outcomes of junior high school students using the Schoology application in mathematics learning are higher than the learning outcomes of junior high school students who carry out conventional mathematics learning.Keywords:Schoology Applications; Mathematics Learning; Student Learning Outcomes.